Use of an ecosystem model for the assessment of the influence of cultivated oysters (Crassostrea gigas) on the nitrogen cycling in the Marennes-Oleron Bay - Bacher, Cedric (1993)
A model of the growth of cultivated oyster in the Marennes-Oléron bay was developped to assess the influence of the nutrients input and of the amount of oysters on the growth performance (Railiard. 1991). The ecosystem main characteristics are: - short residence time of the water. - high turbidity level, depending on the season, tidal level, bathymetry, currents and wind. The turbidity acts on the primary production through light limitation and on oyster production as a food dilution factor. - presence of high density cultivated areas on mid-tidal flats. The amount of oysters is ranging between 80 000 and 110 000 tons according to the year. - spatial variability of the biological and physical features. - coupling effects of the physic process (transport, sedimentation, resuspension) and the biological relationship between the main compartments. Consequently, the system could be described as forced by the residual circulation of water. the input of nutrients from the Charente river, and the presence or absence of cultivated oysters. The combined effects of these factors were assessed with a spatial box model (Raillard. 1991) and enabled to show that the Marennes-Oléron bay had a high carrying capacity. ln order to be compared with other cultivated or natural systems, and with flows measurements, further insight was given to the results yielded by the model. Yearly and seasonal nitrogen budget were therefore computed for every spatial box and for the whole bay. Residence time of the nitrogen was computed for each compartment. The introduction of new compartments and process was discussed as weil as the part played by the cultived oysters as a stabilizing or a control factor of the environment.